Being close(d): How community management on closed media channels contributes to social capital - Lennart Rettler; Ulrike Röttger; Christine Viertmann (Akademische Gesellschaft für Unternehmensführung & Kommunikation, 2023)
The concept of community management has become a significant corporate communications practice. However, users have recently been withdrawing from traditional social media and begun using closed media channels. Closed media channels are communication arenas with restricted access or barriers to entry. The new issue of our publication series Communication Insights explains how companies are using closed media channels for external communications. By analyzing 27 closed media channels by Germany's Top 50 most valuable brands and conducting eight expert interviews Lennart Rettler and Prof. Ulrike Röttger (University of Münster) gained insights into how channels with barriers to entry could be considered a real opportunity for corporate communications departments. – – Community Management in den sozialen Medien ist ein wichtiger und etablierter Bestandteil der Kommunikationsarbeit. Doch dieser Bereich verändert sich seit einiger Zeit. Immer mehr Nutzerinnen und Nutzer ziehen sich aus öffentlichen Social-Media-Kanälen zurück und bevorzugen geschlossene Gruppen mit eingeschränktem Zugang oder Zugangsbarrieren wie auf Telegram. Kommunikationsabteilungen, die sich diesen Trend zunutze machen, können davon profitieren. Prof. Ulrike Röttger und Lennart Rettler (Universität Münster) haben erforscht, wie die 50 am besten bewerteten Unternehmensmarken Deutschlands Closed Media Channels (geschlossene Unternehmenskanäle) in ihrer externen Kommunikation einsetzen und welche Vorteile diese haben. Um die Ergebnisse einzuordnen, wurden zusätzlich Experteninterviews geführt.
Keywords: 650